The Symbolism of Aquatic Women in French Poetry 1890-1899: Purity vs Voluptuousness - Sasin, Eliza (Contrasts in humanities: literature, language, culture, 2023)
Water with its entire seascape, which includes both flora and fauna as well as figures from the mythological world, is one of the main elements of the poetic imagination that forms in the Symbolism. By analysing poems written in the years 1890-99 in the light of the thought of philosophers and mythocritics like Bachelard or Pierrot, we can notice a strong relationship between aquatic symbols and female characters. Focusing on mermaids, nymphs and Aphrodite, we can see that the poetic impressions are created on the basis of a contrast between purity and voluptuousness, which result from the features of the water, the archetypal features of the characters and attributes which are assigned to them during the poetic creation, and that their combination allowed the authors to develop poetic images nuanced and aestheticized relative to the original stories.